Penerapan Family Support Dalam Mengatasi Dissapointment Pada Lansia (Studi Kasus Pada Klien “M” Di Desa Cinta Jaya Kecamatan Pedamaran Kabupaten Ogan Komering Ilir) - Indriani, Indriani; Kusnadi , Kusnadi; Noviza, Neni (CV. ITTC INDONESIA, 2023)
Elderly (Elderly) is the final phase of a person's life who often looks at the past with regret and ignores the future. This is part of the human growth and development process which involves physical, mental and social changes. Elderly people often experience stress, depression and disappointment. Family support is very important in overcoming this problem. The case study of Client